Analysis of gene expression changes in A549 cells induced by organic compounds from respirable air particles - Líbalová, Helena; Krčková, Simona; Uhlířová, Kateřina; Kléma, Jiří; Ciganek, Miroslav; Rössner, Pavel; Šrám, Radim J; Vondráček, Jan; Machala, Miroslav; Topinka, Jan (Mutation research, 2014)
A number of toxic effects of respirable ambient air particles (genotoxic effects, inflammation, oxidative damage) have been attributed to organic compounds bound onto the particle surface. In this study, we analyzed global gene expression changes caused by the extractable organic matters (EOMs) from respirable airborne particles <2.5μm (PM2.5), collected at 3 localities from heavily polluted areas of the Czech Republic and a control locality with low pollution levels, in human lung epithelial A549 cells. Although the sampled localities differed in both extent and sources of air pollution, EOMs did not induce substantially different gene expression profiles. The number of transcripts deregulated in A549 cells treated with the lowest EOM concentration (10μg/ml) ranged from 65 to 85 in 4 sampling localities compared to the number of transcripts deregulated after 30μg/ml and 60μg/ml of EOMs, which ranged from 90 to 109, and from 149 to 452, respectively. We found numerous commonly deregulated genes and pathways related to activation of the aryl hydrocarbon receptor (AhR) and metabolism of xenobiotics and endogenous compounds. We further identified deregulation of expression of the genes involved in pro-inflammatory processes, oxidative stress response and in cancer and developmental pathways, such as TGF-β and Wnt signaling pathways. No cell cycle arrest, DNA repair or pro-apoptotic responses were identified at the transcriptional level after the treatment of A549 cells with EOMs. In conclusion, numerous processes and pathways deregulated in response to EOMs suggest a significant role of activated AhR. Interestingly, we did not observe substantial gene expression changes related to DNA damage response, possibly due to the antagonistic effect of non-genotoxic EOM components. Moreover, a comparison of EOM effects with other available data on modulation of global gene expression suggests possible overlap among the effects of PM2.5, EOMs and various types of AhR agonists.
Keywords: respirační sliznice; lidé; Particulate Matter; Gene Expression Profiling; stanovení celkové genové exprese; pevné částice; Gene Expression; Ah receptor; nádory plic; PAHs; Signal Transduction; nádorové buňky kultivované; Adenocarcinoma of Lung; Microarray Analysis; Humans; mikročipová analýza; PM2.5; adenokarcinom; Gene Expression Regulation, Neoplastic; signální transdukce; adenokarcinom plic; Organic Chemicals; A549 cells; exprese genu; regulace genové exprese u nádorů; Gene expression profile; organické látky; Adenocarcinoma; Respiratory Mucosa; Tumor Cells, Cultured; Lung Neoplasms